Equipment for in situ measurement of machining defects of large aperture optical elements. (17th June 2022) - Tie, Guipeng; Zhou, Haifeng; Shi, Feng; Chen, Jian; Qiao, Shuo; Tian, Ye; Song, Ci
Abstract: A set of in situ measurement equipment of large aperture strong light element based on the principle of laser scattering is established. The size and distribution of defects (damage points) can be judged by the laser scattering signal. The maximum scanning range is 700 mm*1000 mm. The type and size of defects are directly obtained by scanning the quartz sample with a diameter of 100 mm. The types of defects are pitting and scratches, and the width of the scratches and the diameter of the pitting are mostly in the range of 0–10μm. The processing time could reach 31.06s. The device can realize the on‐line in situ measurement of large aperture optical elements, and has the advantages of fast response speed and high measurement accuracy.